COMPUTERIZED SYSTEM OF CASH FLOWS IN AND OUT OF THE KELURAHAN CANDI SEMARANG OFFICE - Devi Ayu Indriyani; Indra Ava Adianta (Journal of Engineering, Electrical and Informatics, 2021)
Cash flow statement is a report on cash receipts and disbursements for a period. Useful for helping employees to assess the amount and uncertainty of future cash flows. Because cash plays an important role in carrying out office operational activities both now and in the future, therefore the office must be able to control the use of cash to ensure that office operations continue to run well. Likewise, the purpose of the research entitled "Computerized System of Cash Inflows and Outflows at the Candi Semarang Village Office" is to find out the smooth operation of the cash situation in the Kelurahan office by making cash flow reports, so that the office can find out the turnover of incoming and cash outflows that occur at the Kelurahan Office, and the Office can control the financial situation in the Kelurahan Office. This study uses a descriptive method, namely describing and analyze data based on existing facts and information. The data collection technique used is by conducting field studies which include observations, interviews and literature studies. Based on the results of the study, it can be concluded that the Candi Semarang Kelurahan office has made a cash flow report in accordance with the applicable Financial Accounting Standards so that in its implementation there are no obstacles.